Algoritmo etapa a etapa para la simulación de cascadas de extracción en fase líquida (2010)
It’s shown and test a stage by stage solution strategy for the set of MESH equations that represents the equilibrium model of the liquid phase extraction process. The simulation algorithm developed is based on liquid/liquid thermodynamics equilibrium and the implementation of isothermal flash and non-isothermal flash calculations, exceeding the scope of graphics and isothermal methods available in literature; also allows specifying variables for heat transfer simulation conditions and different temperature for feed and solvent streams. We illustrate three examples of application related to the separation of acetic acid-water mixture.